RESISTENSI TERHADAP KOLONIALISME DALAM NOVEL GERHANA MERAH KAJIAN POSTKOLONIAL - Danang Bagus Juliantono; Taufik Nurhadi (Buana Bastra, 2019)
This study aims to describe the form of resistance to colonialism in the Red Eclipse novel . The theory used in this study is postcolonialism to see the forms of resistance contained in the novel. In postcolonial theory there are elements of resistance, namely passive resistance and radical resistance, namely hybridity, ambivalence, decolonization and anticolonialism carried out by characters in novels who experience colonialism. The method used in this study, namely a qualitative approach. Data from this study are in the form of words, sentences and paragraphs that describe colonialism in the novel . The data source in this study is the Red Eclipse novel written by Muhammad Sholihin. Data collection in this study uses documentation techniques. The step of analyzing by reading, interpreting and concluding. The results of this study were postcolonial not as something that came after colonialism and signaled the death of colonialism, but more loosely regarded as a resistance to colonial domination, and in the Red Eclipse novel there were two forms of resistance to colonialism namely passive resistance and radical resistance. Passive resistance is shown by the natives with the manifestation of themselves to refuse, namely a resistance that uses other means to maintain cultural identity and ownership. While Radical Resistance acts like an army or combat army, the struggle to liberate the nation from colonialism. organized movement plans, which are carried out by attacking directly.